Differential argument realization in Abui - Kratochvil, Frantisek (2014)
This paper discusses differential argument realization in Abui, a Papuan language (Eastern Indonesia) with semantic alignment (in terms of Donohue and Wichmann 2008; Kratochvíl 2011). The paper examines the roles of volitionality, referential hierarchy, and specificity in differential argument realization (employing light verbs and verbal agreement) and shows that their effects are observable throughout the argument realization system and can be therefore considered the counterpart of differential case marking (DOM/DSM) reported for syntactically aligned, case-marking languages (Bossong 1983; Aissen 2003; Malchukov 2005; Kittilä 2006; de Swart 2007; and others). Although Abui differential argument realization correlates with the referential hierarchy (Bickel 2008), verbal subclasses (in terms of Tsunoda's 1985: 388 affectedness hierarchy) determine whether differential argument realization appears or not (cf. von Heusinger and Kaiser 2011). The paper also considers the diachronic origins of differential argument realization in Abui. Most constructions are argued to originate from two-clause constructions, such as topic/focus constructions gradually merging into singleclause structures. Information-structure related morphemes (light verbs in Abui) serialize with lexical verbs. The process starts with 1st and 2nd person participants (interlocutors) and may extend to human or human-like third persons. Grammaticalization ends in the fusion of the light verb and person prefix, creating new verbal agreement paradigms, as manifested in several central Alor-Pantar languages (Kratochvíl et al. 2011).